Effects of floorball and strength training in a real-life setting on health and physical function in older men - Pedersen, Mogens T.; Bangsbo, Jens (Frontiers in Aging, 2025)
BackgroundThere is lacking information about the physiological response when conducting exercise training of older men in a real-life setting.ObjectivesThe aim of this study was to examine the effects of floorball and strength training in a real-life setting on health and physical function in older men.MethodsSeventy-six sedentary men aged 72.3 ± 0.6 (means ± SE; range: 63–92) years with a height, body mass and body mass index of 178.9 ± 0.8 cm; 92.1 ± 2.2 kg: 28.7 ± 0.6 kg/m2, respectively, were recruited to floorball (FG, n = 29), strength (SG, n = 38) or bowls (BG, n = 9) training 1 h twice a week in municipal activity centers and senior sport clubs. Subjects were tested at baseline, after 12 and 24 weeks.ResultsTwelve weeks of floorball and strength training lead to reduced (P < 0.05) blood glycosylated hemoglobin (Hb1Ac), body mass, fat mass, visceral and android fat. Further, SG had a decrease (P < 0.05) in gynoid fat as well as total and LDL plasma cholesterol. FG and SG decreased heart rate at rest. In SG, systolic and diastolic blood pressure were also reduced (P < 0.05). FG increased (P < 0.05) markers for bone growth. FG and SG improved (P < 0.05) functional capacity. The improvements in FG and SG were maintained after 24 weeks. BG did not have any changes.ConclusionIn conclusion, older men conducting floorball or strength training twice a week in a real-life setting can improve functional capacity and a high number of health factors, whereas playing bowls does not lead to physiological changes.